La Ferrassie 1: New perspectives on a "classic" Neandertal. Issue 117 (April 2018) - Gómez-Olivencia, Asier; Quam, Rolf; Sala, Nohemi; Bardey, Morgane; Ohman, James C.; Balzeau, Antoine
Abstract: The La Ferrassie 1 (LF1) skeleton, discovered over a century ago, is one of the most important Neandertal individuals both for its completeness and due to the role it has played historically in the interpretation of Neandertal anatomy and lifeways. Here we present new skeletal remains from this individual, which include a complete right middle ear ossicular chain (malleus, incus, and stapes), three vertebral fragments, and two costal remains. Additionally, the study of the skeleton has allowed us to identify new pathological lesions, including a congenital variant in the atlas, a greenstick fracture of the left clavicle, and a lesion in a mid-thoracic rib of unknown etiology. In addition, we have quantified the amount of vertebral pathology, which is greater than previously appreciated. We have complemented the paleopathological analysis with a taphonomic analysis to identify any potential perimortem fractures. The taphonomic analysis indicates that no surface alteration is present in the LF1 skeleton and that the breakage pattern is that of bone that has lost collagen, which would be consistent with the intentional burial of this individual proposed by previous researchers. In this study, we used CT and microCT scans in order to discover new skeletal elements to better characterize the pathological lesions and to quantify the fracture orientation of those bones in which the current plaster reconstruction did not allow its direct visualization, which underlines the broad potential of imaging technologies in paleoanthropological research. A century after its discovery, LF1 is still providing new insights into Neandertal anatomy and behavior.